2018
DOI: 10.1002/ejp.1174
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in trigeminal ganglia of male and female rats following chronic constriction of the infraorbital nerve

Abstract: We present novel sex-specific transcriptional regulation in trigeminal ganglia that may contribute to male-/female-based differences in trigeminal neuropathic pain. These findings are expected to open new research horizons, particularly in male versus female targeted therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Very recent gene expression profiling studies have suggested strikingly different chronic pain-related gene expression between the sexes. On examination of 84 genes preselected as relevant to pain, it was 90 observed that chronic constriction injury of the infraorbital nerve in rats regulated the Chrna4 gene in male but not female mice and the Cck, Il1a, Pla2g1b and Tnf genes in female but not male mice. rNA sequencing after chronic constriction injury of the rat sciatic nerve 91 showed that only 6% of genes examined (862 of 14,403) were differentially expressed by the sexes at the baseline; however, of the 3,127 genes regulated by the injury in either sex, only 514 (16%) were common to both males and females, and in nine cases were regulated in opposite directions in male and female rats 91 .…”
Section: Pleiotropymentioning
confidence: 99%
“…Very recent gene expression profiling studies have suggested strikingly different chronic pain-related gene expression between the sexes. On examination of 84 genes preselected as relevant to pain, it was 90 observed that chronic constriction injury of the infraorbital nerve in rats regulated the Chrna4 gene in male but not female mice and the Cck, Il1a, Pla2g1b and Tnf genes in female but not male mice. rNA sequencing after chronic constriction injury of the rat sciatic nerve 91 showed that only 6% of genes examined (862 of 14,403) were differentially expressed by the sexes at the baseline; however, of the 3,127 genes regulated by the injury in either sex, only 514 (16%) were common to both males and females, and in nine cases were regulated in opposite directions in male and female rats 91 .…”
Section: Pleiotropymentioning
confidence: 99%
“…Altered gene expression patterns in the DRG (Hammer et al, 2010; Raju, Englander, Capobianco, Tsinoremas, & Lerch, 2014) and TG (Korczeniewska et al, 2018) following peripheral nerve injury have been implicated in the aetiology of NP, which nevertheless remains elusive. Kogelman et al investigated gene expression levels in the DRG and TG of the naïve rats and identified genes that were differentially expressed between the two ganglia (Kogelman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The gene Chrna4, coding for the neuronal acetylcholine receptor subunit alpha-4 (nAChRα4), displayed signi cant downregulation in DRG in males only. Previously, CCI of the infraorbital nerve in rats showed greater mechanical allodynia and increased expression of Chrna4 in females [39]. With an overall sex-dependent change in the same direction, and the fact that nicotinic receptors (of which nAChRα4 is one) mediate fast depolarisations at synapses [81], upregulation of Chrna4 might sensitize neurotransmission in a sex-speci c manner.…”
Section: Neuronal Transmissionmentioning
confidence: 93%
“…Previous studies have reported varying results in sex differences in behaviour following PNI. For example, greater mechanical allodynia in female rats has been reported in at least one PNI study and, in another study, following CCI of the infraorbital nerve [8,39]. In two other studies, no behavioural differences were reported, even though differences in the mechanisms of putative sex differences were hypothesized [9,10].…”
Section: Behavioural Testsmentioning
confidence: 94%